Persoalan Pengangguran dan Kewajiban Kerja Menurut Al Syaibani - Ridlo, Ali (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2022)
The purpose of this study was to describe the problem of unemployment and work obligations according to al-Syaibani, using qualitative research methods and a literature study approach. The results of the study showed that the total unemployment rate in the period 2014 to 2018 was still fluctuating, and the average unemployment rate in that period of 100 Indonesians is 6 people who were unemployed. Meanwhile, according to Al-Syaibani, work was obligatory. Al-Syaibani also argued that everyone needed labor from others based on their expertise. The distribution of work was an economic object that had two aspects simultaneously, namely the economic aspect and the religious aspect. The problem of unemployment was an economic problem, so that all elements, both the government and the community, needed synergy in reducing the unemployment rate in Indonesia.